Seleção de Sensores em Redes de Sensores Sem Fio Heterogêneas para Cidades Inteligentes - Siqueira Júnior, Francisco de Assis (2016)
Despite being a well-established technology, research inWireless Sensor Networks (WSNs) are facing challenges due to its intrinsic connection to the paradigms of Smart Cities and IoT (Internet of Things - IoT). Traditionally, WSNs are deployed to meet the needs of a single application and are composed of sensors with the same physical characteristics. However, when considering smart environments, where several objects can collect data, trigger actions and interact with each other in order to provide sophisticated services, it is easy to see the diversity of the applications that can perform requests in such environments. It is also possible that different types of equipment interact with each other, such as sensors with different physical characteristics, thus creating a Heterogeneous WSN (HWSN). For this reason, this work aims to contribute to the management of HWSNs in Smart Cities environments by proposing an approach for dynamic and on-demand selection of sensors. This selection is performed by taking into account the physical characteristics of the sensors and the applications’ demands. This approach has been integrated into the POlicy-based Sensor SElection in Heterogeneous Wireless Sensor Network framework (POSSE-HWSN), which was implemented in order validate the proposal. Tests have shown that by using POSSE-HWSN it was possible to select the sensors with the most suitable hardware features to meet every application needs, thus improving the selection efficacy.